Failure Leads Protest Movements to Support More Radical Tactics - Louis, Winnifred R.; Lizzio-Wilson, Morgana; Cibich, Mikaela; McGarty, Craig; Thomas, Emma F.; Amiot, Catherine E.; Weber, Nathan; Rhee, Joshua; Davies, Grace; Rach, Timothy; Goh, Syasya; McMaster, Zoe; et al. (Social psychological & personality science, 2022)
Most social movements will encounter setbacks in their pursuit of sociopolitical change. However, little is known about how movements are affected after protestors fail to achieve their aims. What are the effects of failure on subsequent engagement in various conventional and radical actions? Does failure promote divergent reactions among protestors and/or dissatisfaction with democracy? A meta-analysis of nine experiments (N = 1,663) assessed the effects of one-off failure on protestors’ reactions, subsequent tactical choices, and support for democracy; and iterative stochastic simulations modeled the effects of failure over multiple protests over time. Results indicated that initial failure gives rise to divergent, somewhat contradictory responses among protestors and that these responses are further influenced by the repeated failure (vs. success) over time. Further, the simulations identified “tipping points” in these responses that promote radicalization and undermine support for democracy.